Examining the Entrepreneurship Intention (El) among hospitality undergraduates in higher learning institution: a case study at UiTM Terengganu / Muhammad Lukman Shahrul Azman - Shahrul Azman, Muhammad Lukman (2021)
This paper aims to examine the correlation and the relationship on the factors influencing entrepreneurship intention (El) among hospitality undergraduates in higher learning institution. Since most literature agreed that entrepreneurial intention can be determined by using Theory of Planned Behavior (TPB), this theory is adapted as theoretical framework in this study. The independent variables of this study comprise attitude, perceived support and barriers, locus of control (LoC) and need for achievement (nAch). The sample of this study is from hospitality undergraduates at UiTM Terengganu with approximately 484 total of population. The findings of this study show that there is a positive correlation between all independent variables towards entrepreneurship intention (El). It also appears that there is significant relationship between all independent variables towards entrepreneurship intention (El).